Smart Parking Space Detection Using Advanced Deep Learning Techniques - Aguswandi, Lalu Heri; Triwijoyo, Bambang Krismono; Martono, Galih Hendro (Politeknik Negeri Lhokseumawe, 2025)
This study aims to develop an accurate and efficient empty parking slot detection model to assist users in finding parking spaces. The developed model utilizes YOLOv11 as a pretrained model and demonstrates excellent performance with a precision of 99%, recall of 99%, and a Mean Average Precision (mAP) of 99%. These results validate the model's ability to accurately detect empty parking slots with 100 training epochs. Additionally, the model operates in real-time with a frame rate of 25 frames per second (FPS)